Deciphering the Nexus: Analysing Social Dynamics in Cybercrime Investigations through Interpretive Structural Modeling in Forensic Science - Monika Singh; Manjeet Kumar; Vinny Sharma (Indian Journal of Forensic Medicine and Pathology, 2025)
Cybercrime has evolved into a pervasive and multifaceted challenge, inÁuenced by an array of social factors that often confound traditional forensicmethodologies. This paper endeavors to identify and analyze key social factors contributing to cybercrime investigations within the domain of forensic science. Employing Interpretive Structural Modeling (ISM), this study delves into the intricate interrelationships among these social factors to provide a comprehensive understanding of their impact on cybercrime investigations. Through an exhaustive literature review, signi𿿿cant social factors inÁuencing cybercrime forensics areidenti𿿿ed and analyzed. Drawing upon empirical evidence and expert insights, an ISM model is constructed to visualize the complex network of interactions among these factors. The model serves as a valuable tool for elucidating the dynamics of cybercrime investigations and identifying areas for intervention and improvement. The 𿿿ndings of this study underscore the profound nÁuence of social factors on cybercrime investigations, shedding light on the complexities inherent in forensic analysis of digital crimes. By recognizing and understanding these social dynamics, forensic practitioners and law enforcement agencies can develop more effective strategies and methodologies for combating cyber threats and prosecuting cybercriminals.